2023
DOI: 10.1177/03611981231152459
|View full text |Cite
|
Sign up to set email alerts
|

Freeway Congestion Management With Reinforcement Learning Headway Control of Connected and Autonomous Vehicles

Abstract: Adaptive cruise control (ACC) systems are increasingly offered in new vehicles in the market today, and they form a core building block for future full autonomous driving. ACC systems allow vehicles to maintain a desired headway to a leading vehicle automatically. Recent research demonstrates that (1) shorter headways lead to higher throughput, and (2) the effective use of ACC can improve traffic flow by adapting the desired time headway in response to changing traffic conditions. In this paper we show that, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…• Ramp only control yielded better results than ramp and mainline control: It has been observed that the delay performance was the best when the ramp sections only were controlled as opposed to controlling the ramp and mainline sections together. This has been observed in our earlier work [35] and can be justified by the fact that the freeway delay contributes heavily to the system delay as opposed to the ramp delay due to the relatively higher freeway demand. Also, animated traffic simulations have shown that any speed disturbances on the freeway (to adjust the headway) will cause spillback and affect the whole freeway stream thereby affecting the delay of more vehicles as opposed to the ramp delay which may have a local effect on the corresponding ramp vehicles only.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…• Ramp only control yielded better results than ramp and mainline control: It has been observed that the delay performance was the best when the ramp sections only were controlled as opposed to controlling the ramp and mainline sections together. This has been observed in our earlier work [35] and can be justified by the fact that the freeway delay contributes heavily to the system delay as opposed to the ramp delay due to the relatively higher freeway demand. Also, animated traffic simulations have shown that any speed disturbances on the freeway (to adjust the headway) will cause spillback and affect the whole freeway stream thereby affecting the delay of more vehicles as opposed to the ramp delay which may have a local effect on the corresponding ramp vehicles only.…”
Section: Discussionsupporting
confidence: 60%
“…This approach is conceptually similar to the RL control studies in [30][31][32][33][34]. In our previous work in [35], we demonstrated that although tighter headways improve road capacity and traffic congestion, a breakdown can still occur at higher densities, which required further attention and more elaborate dynamic optimal headway control near bottlenecks. Therefore, we proposed and developed an adaptive DRL headway controller that varies headways at the infrastructural level, that is, on a segmentby-segment basis, to optimize traffic flow and minimize delay.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations